Otimização de método analítico para determinação de etanol em Succinato de Metoprolol por cromatografia em fase gasosa rápida - Vissotto, Juliano Parizotto (2023)
Residual solvents are substances that are present in many stages of the drug manufacturing process. Coating of Metoprolol Succinate tablets uses the solvent ethanol, and its presence must be determined in order to ensure that residual levels do not exceed the acceptable limits recommended by toxicological safety guides. In this work, a conventional analytical method by gas chromatography and headspace sampling was developed and validated for identification and quantification of the residual solvent ethanol in Metoprolol Succinate 100 mg coated tablet. The selectivity of the method evidenced a resolution greater than 1,5 for the analyte of interest and the linearity exhibited a coefficient correlation greater than 0,99, demonstrating a linear correlation between the analytical response and the increased concentration. The method obtained precision and accuracy in accordance with guides for acceptance criteria, and it was able to resist small variations intrinsic to the analysis. Variations in chromatographic column dimensions, heating rate, sample division rate, carrier gas flow were the tests performed, according to the concepts of fast gas chromatography, aiming to reduce the total analysis time. The quick method was validated, based on the optimizations performed, and compared with the conventional method in terms of analytical frequency of work on the equipment. The validated method proved to be 2,2 times quicker than the conventional method, meeting the validation requirements. Therefore, quality control can use the validated method in processes to control residual solvents in drugs, with greater efficiency, reducing analysis time, as well as generating safe and reliable results.